2000
DOI: 10.1021/ma992031o
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mechanical and Electrical Percolation during the Gelling of Nafion Solutions

Abstract: Rheological and impedance measurements are performed on Nafion solutions at relatively high concentration. The viscosity scales with the Nafion volume fraction as ηr ∝ φ0.59, up to φ = 2.5%. At higher fractions the viscosity diverges. At φ = 2.5% the storage modulus exhibits scaling behavior with the frequency (G‘ ∝ ω0.81), and the solution behaves as a gel. The results for the viscosity seem to fit the Zimm, rather than the Rouse, model. For the sodium form of Nafion the conductivity behaves qualitatively the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The results may also indicate a network structure through electrostatic interactions in which low shear rates only partially distort the structure. In support of the latter, it has been reported that the storage modulus becomes frequency‐independent at or below 15 °C; this is indicative of a network,16 and the temperature is not substantially lower than the temperature herein. The evidence may suggest a model for PFSA polyelectrolyte liquid dispersions in which charge‐stabilized, anisotropic, and potentially overlapping particles exist on a deformable three‐dimensional lattice, with the particle centers of mass at the lattice points.…”
Section: Discussionsupporting
confidence: 71%
“…The results may also indicate a network structure through electrostatic interactions in which low shear rates only partially distort the structure. In support of the latter, it has been reported that the storage modulus becomes frequency‐independent at or below 15 °C; this is indicative of a network,16 and the temperature is not substantially lower than the temperature herein. The evidence may suggest a model for PFSA polyelectrolyte liquid dispersions in which charge‐stabilized, anisotropic, and potentially overlapping particles exist on a deformable three‐dimensional lattice, with the particle centers of mass at the lattice points.…”
Section: Discussionsupporting
confidence: 71%
“…is consistent, at least qualitatively, with the of non-freezable water molecules in a PFSA membrane is reported findings of conductivity and sorption behavior of PFSA membranes to correspond to l w 6-7, independent of the initial water content in this regime ð15 < l < 22Þ [20,35]. The conductivity of the PFSA of the membrane at room temperature [36,38,39,46,62], with the membranes increases during water uptake [6,8,32,[34][35][36][37][38][39]59], remaining water, if any, being freezable. Thus, the higher the probably due to larger hydrophilic domains [2,[6][7][8]19,35,39,45,59].…”
supporting
confidence: 80%
“…The conductivity of PFSA membranes, k c , increases with water uptake (or swelling) [3,5,6,8,[32][33][34][35][36][37][38][39] and is assumed to be related to the water volume fraction according the equation, k c ff s w where the exponent, s, is empirically determined to be between 1.0 and 1.95 [8,33,35,36]. This relationship can be attributed to the growth of water-swollen ionic domains: both the interconnecting channels and spheres expand during water sorption [6,10,21,35,[39][40][41].…”
mentioning
confidence: 99%
“…To investigate the structure and swelling behavior of the hydrated Nafion membranes, numerous experimental efforts have been concentrated on neutron, wide and small angle X-ray scattering, infrared (IR) and Raman spectroscopy, and transmission electron microscopy (TEM) techniques. [1][2][3][4][5][6][7][8][9][10][11][12][13] It has been well established that hydrated Nafion membranes have two phases on a nanometer scale, a hydrophobic phase containing the backbone and a hydrophilic phase containing sulfonic acid groups and water. Several models for these structures such as the interconnected spherical water clusters (the cluster-network model) have been proposed for the interpretation of the scattering patterns.…”
mentioning
confidence: 99%
“…Several models for these structures such as the interconnected spherical water clusters (the cluster-network model) have been proposed for the interpretation of the scattering patterns. [1][2][3][4][5][6][7] However, these models are still under discussion concerning the size and shape of the water clusters. It is meaningful to clarify the structure of the membranes for analytical study and to improve the mechanical and transport properties of the materials.…”
mentioning
confidence: 99%